(3GdOQI GdSfjI aj TQM GdebOeI GdYTeGhjIs - (3eMeO CUjd Hf eMeO GdCfUGQj GdHQOjSjs; (3YHO GdHGQj GdYTeGhj GdQaGYj, CHhGdYHGSs
(3ChdgG (B:s
(3NUhUkG Yde GdaJGhGJ eY GdTQGFY hGdCQcGf s
(3BNQgG (B:s
(3hLejd GdCOH eYjf Ydi WdH GdYde hdGMhd hdG bhI EdG HGddg GdYdj GdYXje s
(3GdebOeI GdYTeGhjI GfXQ EjVGM Gdecfhf L (B2 (3U` (B544s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdeGdcjs